2018
DOI: 10.1073/pnas.1804599115
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a common immune regulatory pathway induced by small heat shock proteins, amyloid fibrils, and nicotine

Abstract: Although certain dogma portrays amyloid fibrils as drivers of neurodegenerative disease and neuroinflammation, we have found, paradoxically, that amyloid fibrils and small heat shock proteins (sHsps) are therapeutic in experimental autoimmune encephalomyelitis (EAE). They reduce clinical paralysis and induce immunosuppressive pathways, diminishing inflammation. A key question was the identification of the target for these molecules. When sHsps and amyloid fibrils were chemically cross-linked to immune cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…Previously, a study showed neuroprotection of nicotine from Aβ-induced neurotoxicity (Rothbard et al, 2018 ). Here, we examined nicotine effects on HT-22 cell viability after the application of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a study showed neuroprotection of nicotine from Aβ-induced neurotoxicity (Rothbard et al, 2018 ). Here, we examined nicotine effects on HT-22 cell viability after the application of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…5e-g). It is to be noted that other inflammatory modulators such as nicotine also suppresses EAE 40 . Nicotine mediated NFκB suppression involves down regulation of p65/p50 subunits of NFκB and blocking its binding to DNA 41 .…”
Section: Discussionmentioning
confidence: 99%
“…34 A group in France proposed a potential role of nicotine as the agent responsible for smoking's action on the ACE2 receptor, potentially providing a protective mechanism for smoking in COVID-19. Nicotine is also of interest because it could help in COVID-19 by mitigating a host of destructive inflammatory reactions 35,36 that often are associated with deterioration in the later stages of COVID-19. 37,38 Another mechanism of interest is nitric oxide (NO) which is one of the many chemicals found in cigarette smoke, and also relevant to nicotine.…”
Section: Discussionmentioning
confidence: 99%